Development of a monoclonal antibody with equal reactivity to ustiloxins A and B for quantification of main cyclopeptide mycotoxins in rice samples. (October 2018) - Fu, Xiaoxiang; Wang, Weixuan; Li, Yuying; Wang, Xiaohan; Tan, Guiyu; Lai, Daowan; Wang, Mingan; Zhou, Ligang; Wang, Baomin
Abstract: Rice false smut (RFS) is one of the most destructive diseases in majority of rice growing areas around the world. Ustiloxins A (UA) and B (UB) are the main cyclopeptide mycotoxins (>90%) among all characterized ustiloxins which are produced by the RFS pathogen Villosiclava virens . Rapid diagnosis of ustiloxins is essential to assess the safety of rice food and feed contaminated with the pathogen. In this study, a monoclonal antibody (mAb) with equal reactivity to UA and UB, which was named as mAb 4C4F11, was successfully screened. After optimization, the sensitivity, selectivity and accuracy of the direct competitive enzyme-linked immunosorbent assay (dc-ELISA) for simultaneous detection of the total content of UA and UB in rice samples was explicated. The concentration causing 50% of inhibition (IC50 ) was 13.0 ng/mL for UA or UB, the limit of detection (LOD) was 0.7 ng/mL, and the calibration range was from 2 to 76 ng/mL. The LOD and limit of quantification (LOQ) of UA plus UB in rice were 35 and 100 ng/g, respectively. Average recoveries of UA or UB from the spiked RFS balls and grains were between 84.1% and 102.5% with coefficient of variation less than 15%. The developed immunoassay can be employed as a rapid, effective and accurate method for detection of main ustiloxins in RFS balls as well as rice food and feed samples. Highlights: A monoclonal antibody with equal reactivity to ustiloxins A and B was screened. A dcELISA was developed for simultaneous detection of ustiloxins A and B. Main ustiloxin contents tested by the dc-ELISA agreed well with those by HPLC. The established assay provides a method for detection of ustiloxins A and B.